WILLPOWER IN STRESSFUL SITUATIONS: THEORY AND PRACTICE - Nigora Yuldasheva; Zamira Baxtiyarovna Bilolova (Modern American Journals, 2025)
This article discusses the general concept of will, the factors that shape it, especially the process of making volitional decisions in stressful situations. It also describes the volitional attitude of people of different ages to stress, the role of the social environment, and methods of strengthening willpower through psychological training and exercises.